Pedagogia da notícia : uma rota de aprendizagem para o consumo consciente da informação jornalística no ambiente digital - Oselame, Mariana Corsetti (2020)
Inserted in the broad subject area of Applied Social Sciences, in field of Communication Sciences and in the interface between Communication and Education, this critical reflection of a philosophical nature and propositional character presents the following research question: what is the role of the Brazilian media and journalists in combating disinformation in the digital environment? To answer this question, this study adopts the critical method (POPPER, 2006) and proposes, as a general objective, the construction of a practical, viable and scalable solution to the problem that originated this reflection. As specific objectives, this study aims to: 1) contextualize Media Ecology as a possible theoretical support for understanding the current media landscape; 2) identify the main characteristics of the technological environment in which we operate; 3) understand the specifics of the society created by the digital environment; 4) adapt the concept of conscious consumption to the universe of information; 5) discuss the role of emotions in times of post-truth, disinformation and infotoxicity; 6) map the range of initiatives related to media education, as well as their conceptual variations and areas of activity; and 7) to propose the concept of News Pedagogy and a way to operationalize it within the scope of the informal education system. This research is based on three assumptions. The first reaffirms the need to combat not only the spread of fake news, but also the other strategies that promote disinformation and infotoxicity in the post-truth era, in that beliefs overlap with empirically verifiable facts. The second considers that this fight should be institutionalized through public policies aimed at media education and complemented with the engagement of the most diverse sectors of society, including the media and journalists themselves. A third assumption of this study maintains that, given the fragility of these public policies aimed at media education in Brazil, the media and professionals of the press can - and must, as part of their social responsibility – assume a central role in combating disinformation. More than signaling what is fact and what is fake, they can be the promoters of conscious consumption based on the application of the assumptions contained in News Pedagogy and its learning path.